Multistep binding of transition metals to the H-N-H endonuclease toxin colicin E9. - Keeble, A; Hemmings, A; James, R; Moore, G; Kleanthous, K (2002)
We report the first stopped-flow fluorescence analysis of transition metal binding (Co(2+), Ni(2+), Cu(2+), and Zn(2+)) to the H-N-H endonuclease motif within colicin E9 (the E9 DNase). The H-N-H consensus forms the active site core of a number of endonuclease groups but is also structurally homologous to the so-called treble-clef motif, a ubiquitous zinc-binding motif found in a wide variety of metalloproteins. We find that all the transition metal ions tested bind via multistep mechanisms. Binding was further dissected for Ni(2+) and Zn(2+) ions through the use of E9 DNase single tryptophan mutants, which demonstrated that most steps reflect conformational rearrangements that occur after the bimolecular collision, many common to the two metals, while one appears specific to zinc. The kinetically derived equilibrium dissociation constants (K(d)) for transition metal binding to the E9 DNase agree with previously determined equilibrium measurements and so confirm the validity of the derived kinetic mechanisms. Zn(2+) binds tightest to the enzyme (K(d) approximately 10(-)(9) M) but does not support endonuclease activity, whereas the other metals (K(d) approximately 10(-)(6) M) are active in endonuclease assays implying that the additional step seen for Zn(2+) traps the enzyme in an inactive but high affinity state. Metal-induced conformational changes are likely to be a conserved feature of H-N-H/treble clef motif proteins since similar Zn(2+)-induced, multistep binding was observed for other colicin DNases. Moreover, they appear to be independent both of the conformational heterogeneity that is naturally present within the E9 DNase at equilibrium, as well as the conformational changes that accompany the binding of its cognate inhibitor protein Im9.